2018
DOI: 10.1186/s13054-018-2243-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adrenomedullin estimates survival and reversibility of organ failure in sepsis: the prospective observational multinational Adrenomedullin and Outcome in Sepsis and Septic Shock-1 (AdrenOSS-1) study

Abstract: BackgroundAdrenomedullin (ADM) regulates vascular tone and endothelial permeability during sepsis. Levels of circulating biologically active ADM (bio-ADM) show an inverse relationship with blood pressure and a direct relationship with vasopressor requirement. In the present prospective observational multinational Adrenomedullin and Outcome in Sepsis and Septic Shock 1 (, AdrenOSS-1) study, we assessed relationships between circulating bio-ADM during the initial intensive care unit (ICU) stay and short-term out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
89
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 21 publications
4
89
0
5
Order By: Relevance
“…Anyway, normalization of lactate is associated with improved outcome [4]. We have recently shown that plasma levels of bio-adrenomedullin (bio-ADM), a peptide regulating vascular integrity and endothelial function, were associated with patient outcome during sepsis [5]. Interestingly, we observed that patients with elevated bio-ADM levels at admission and with low bio-ADM levels 2 days later had similar outcome to patients with persistently low bio-ADM levels.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…Anyway, normalization of lactate is associated with improved outcome [4]. We have recently shown that plasma levels of bio-adrenomedullin (bio-ADM), a peptide regulating vascular integrity and endothelial function, were associated with patient outcome during sepsis [5]. Interestingly, we observed that patients with elevated bio-ADM levels at admission and with low bio-ADM levels 2 days later had similar outcome to patients with persistently low bio-ADM levels.…”
mentioning
confidence: 86%
“…The AdrenOSS-1 study is a prospective observational study conducted in 24 centers within 5 European countries and included 583 septic patients from June 2015 to May 2016 [5]. The primary endpoint was 28-day mortality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with bio-ADM > 70 pg mL -1 at admission, decrease in bio-ADM below 70 pg mL -1 at day 2 was associated with recovery of organ function at day 7 and better 28-day outcome (9.5% mortality). Constantly elevated bio-ADM at day 2 was linked to prolonged organ dysfunction and high 28-day mortality (38.1% mortality, HR = 4.9, 95% CI: 2.5-9.8) [49]. Preclinical work performed with the non-neutralizing ADM-binding antibody adrecizumab in animal models of septic shock revealed improved vascular barrier function, reduced vasopressor dosage and organ dysfunction and increased survival.…”
Section: Role Of Mid-regional Fragment Of Pro-adrenomedullin In Sepsismentioning
confidence: 99%